2010
DOI: 10.1007/s13187-010-0170-2
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cancer Awareness Among Undergraduate Dental Students in Iran

Abstract: The aim of this study was to assess undergraduate dental students' knowledge about prevention and detection of oral cancer in Tehran University of Medical Sciences (TUMS). A validated questionnaire which tested oral cancer awareness and procedure was given to 3rd to 6th year students of the dental faculty of TUMS. A total of 165 students participated in this survey. As expected, students of the final years showed greater knowledge of risk factors and clinical features of the disease. This study highlights for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
45
2
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 16 publications
9
45
2
5
Order By: Relevance
“…Hence, it may have limited generalizability. Several cross-sectional questionnaire-based studies conducted among dental students evaluating the awareness of oral cancer had included questions related to TUC counseling (Jaber et al, 1997;Uti and Fashina, 2006;Carter and Ogden, 2007;Ogden and Mahboobi, 2011) but the study conducted by Chowdhury et al (2010) had given equal importance in evaluating the awareness of oral cancer and attitudes towards tobacco control among dental students. This Bangladeshi study used the Global Health Professionals Student Survey (GHPSS) instrument for evaluating TUC counseling and the modified 32-item Humphris Oral Cancer Knowledge Scale (HOCKS) for evaluating oral cancer awareness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it may have limited generalizability. Several cross-sectional questionnaire-based studies conducted among dental students evaluating the awareness of oral cancer had included questions related to TUC counseling (Jaber et al, 1997;Uti and Fashina, 2006;Carter and Ogden, 2007;Ogden and Mahboobi, 2011) but the study conducted by Chowdhury et al (2010) had given equal importance in evaluating the awareness of oral cancer and attitudes towards tobacco control among dental students. This Bangladeshi study used the Global Health Professionals Student Survey (GHPSS) instrument for evaluating TUC counseling and the modified 32-item Humphris Oral Cancer Knowledge Scale (HOCKS) for evaluating oral cancer awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the oral cancer awareness of dental students (Jaber et al, 1997;Carter and Ogden, 2007;Ogden and Mahboobi, 2011). On the other hand, the effectiveness of tobacco use cessation (TUC) counseling in dental office and the fact that the performance of these programs can be as effective in dental practice as in other primary health care settings are well documented (Warnakulasuriya, 2002;Carr and Ebbert, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the general male population, oral cancer is the fifth most frequent, and in northeastern Brazil (7.16 cases per 100 thousand) it is the fourth 4 . Squamous cell carcinoma (SCC) accounts for 95% of oral cancers and, in addition to being associated with avoidable etiological risk factors, it affects the tissue lining of the mouth, which is perfectly visible to dentists during routine examination 3,5 .…”
Section: Introductionmentioning
confidence: 99%
“…The higher the stage, the worse the prognosis 8 . Deficiencies in training, which hinder the recognition of lesions, contribute to the delayed diagnosis 2,5 . The early diagnosis is essential to achieve the best results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation